OPINION NO. 128 OF FRENCH NATIONAL CONSULTATIVE ETHICS COMMITTEE FOR HEALTH AND LIFE SCIENCES (CCNE) ON “THE ETHICAL ISSUES OF AGEING” - RIALLE, Vincent (MEDECINE LEGALE DROIT MEDICAL, 2025)
This Opinion denounces a state of advanced deterioration of our caring modalities for fragile or vulnerable old people, whose economic precariousness and social isolation leave no other choice than “placement” in “Host establishments for dependent elderly people”. Going beyond the mere description of unbearable situations, the Opinion expresses an unprecedented call for urgent and radical changes in all areas and at all levels of the society for thinking differently about aging, for restoring to frail and vulnerable older people their full place in our society, changing mentality and vocabulary regarding elders, bringing about an epistemological revisiting of the whole health system, and a renewed training of health and social actors, for creating new forms of solidarity, and significantly strengthening the policies accompanying ageing.